Satisfaction of Parents and Caregivers with Dental Treatment of Children Under General Anesthesia in a Day Care Surgery Setting - Bruno Špiljak; Vlaho Brailo; Bernard Janković; Dragana Gabrić; Marin Lozić; Vasilije Stambolija; Danica Vidović Juras; Zoran Karlović; Željko Verzak (University of Zagreb. School of Dental Medicine, 2022)
Objective: The aim of this study was to examine the satisfaction of parents and caregivers of patients who underwent dental treatment in general anesthesia (GA) in a day-care surgery setting. Material and Methods: Anonymous questionnaire was sent to parents/caregivers of patients who underwent full mouth restoration in GA. The survey consisted of 4 parts: general data, data about procedure, satisfaction with various aspects of care and the perception of parents/caregivers about the condition of their child in relation to the time before dental treatment in GA. Results: 66 parents/caregivers (30.5%) responded to the questionnaire. Overall satisfaction with the treatment was high (4.69). Respondents expressed the highest degree of satisfaction with communication with nurses (4.92), and the lowest with the waiting time for the procedure (3.89). Parents/caregivers of patients who reported difficulty eating expressed significantly lower overall satisfaction than the subjects whose children did not report difficulty eating. Also, the more treatments the patients underwent, the lower was the overall satisfaction than of those subjects whose children were never treated in such a manner before. Conclusions: Since patient satisfaction has a beneficial impact on treatment outcome and adherence to preventive recommendations, all health care providers should strive to achieve it.